MANIFESTASI TINDAK TUTUR DALAM LIRIK LAGU DANGDUT DENGAN PERSPEKTIF PRAGMATIK - Nur Lailiyah Nur; Andri Pitoyo; Marista Dwi Rahmayantis; Sempu Dwi Sasongko; Chelya Ilham R. P. (Jurnal Semantik, 2024)
This study aims to identify the forms of speech acts and people's perceptions of language use in the four lyrics of the dangdut songs Mangku Purel (MP), Nemen (N), Runtak (R), and Rasah Nyangkem 3 (RN3). The primary data sources for this research are four dangdut song lyrics, while the secondary data sources come from 200 people who enjoy dangdut songs. The research data is in the form of utterances in four dangdut song lyrics. The results of the study show that of the four song lyrics, speech acts are found, namely: assertive, directive, expressive, and commissive. Expressive speech acts are most often used and are in the form of sarcasm. Meanwhile, the public's perception of the use of language in the four dangdut song lyrics shows the low level of language use used by the authors in composing dangdut songs. Based on the questionnaire that was distributed, of the four song lyrics, an average of 86% stated that the use of language was not good. This research can contribute to artists paying more attention to the use of language in writing song lyrics, so that songs are not just entertainment, but also social control.